Biomechanical evaluation of a fixation technique with a modified hemicerclage for tibial tuberosity transposition: an ex vivo cadaveric study - Natsios, Pavlos; Capaul, Rahel; Kopf, Norbert; Pozzi, Antonio; Tinga, Selena; Park, Brian (Frontiers in Veterinary Science, 2024)
Objectives: 1) to determine stiffness, load at failure, and mode of failure of a novel fixation method with a tension modified-hemicerclage (MH) for tibial tuberosity transposition, and 2) to compare the biomechanical properties of this novel fixation technique to 2 pins (2Pins) and 2 pins and tension band wire fixation (2Pins+TBW). Study design/Methods: Thirty cadaveric stifles from dogs between 5.2 and 13.1 kg were assigned to 3 treatment groups: Group 1: fixation technique with MH; Group 2: 2Pins; Group 3: 2Pins+TBW. Biomechanical testing was performed with the tibia positioned at an angle of 135 relative to vertical position. Tensile force was applied to the patellar ligament until catastrophic failure was observed. The mode of failure, the load at failure, and the stiffness were compared among treatment groups. Results: The mean stiffness of the novel fixation (38.1 N/mm ± 7.1) and the 2Pins+TBW (40.2 N/mm ± 9.3) were greater than the 2Pins (26.7 N/mm ± 6.7). There was no significant difference between the novel fixation technique and 2Pins+TBW in stiffness and maximumtotal load to failure load. The 2Pins (284.3N ± 70.5) failed at a significantly lower load than the tension modified-hemicerclage (555.7N ± 225.9N) and 2Pins+TBW (715.3N ± 339.8N). Discussion/Conclusion: A fixation technique using a modified hemicerclage had the same strength and stiffness as the 2Pins+TBW and was stronger and stiffer than the 2 Pins technique in a cadaveric model.